Pharmacotherapeutic potential of pomegranate in age-related neurological disorders - Emami Kazemabad, Mohammad Javad; Asgari Toni, Sara; Tizro, Neda; Dadkhah, Parisa Alsadat; Amani, Hanieh; Akhavan Rezayat, Shima; Sheikh, Zahra; Mohammadi, Mohammad; Alijanzadeh, Dorsa; Alimohammadi, Farnoosh; Shahrokhi, Mehregan; Erabi, Gisou; et al. (Frontiers in Aging Neuroscience, 2022)
Age-related neurological disorders [AND] includes neurodegenerative diseases [NDD] such as Alzheimer disease [AD] and Parkinson disease [PD], which are the most prevalent types of de-mentia in the elderly. It also includes other illnesses such as migraine and epilepsy. AND’s are multifactorial, but aging is their major risk factor. The most frequent and important pathologi-cal features of AND are oxidative stress, inflammation, and accumulation of misfolded pro-teins. As AND's brain damage is a significant public health burden and its incidence is increas-ing, much has been done to overcome it. Pomegranate (Punica granatum L.) is one of the poly-phenol-rich fruits which is widely mentioned in medical folklore. Pomegranate is commonly used to treat common disorders such as diarrhea, abdominal pain, wound healing, bleeding, dysentery, acidosis, microbial infections, infectious and non-infectious respiratory diseases, as well as neurological disorders. In the current review article, we aimed to summarize the data on pharmacotherapeutic potentials of pomegranate in age related neurological disorders.